Estudo de Diplodon (D.) Besckeanus (Dunker, 1849) existente na Lagoa de Juturnaíba, município de Araruama, Estado do Rio de Janeiro, Brasil (Bivalvia, Unionoidea, Hyriidae) - Alvarenga, Luiz Carlos de Figueiredo (1978)
Studies achieved on a population of the freshwater mussel Diplodon (Diplodon) besckeanus (Dunker,1849), as well as some ecological data from its habitat. Systematical subjects are treated together with comments on synonymy and the characterization of the higher taxa under which this species is subordinated. A more accurated attention was given to the morphological aspects of the shell and the larval phasis, although the morphology of soft parts had been sometimes pointed out with the scope of seeking specific characters which could be compared with the results obtained by other authors who have worked in other species of the same genus. Some observations on behavior are added. Physical and chemical data with regard to the biotope were taken from just one point. This sampling was done preferably once in each season lasting for twenty four hours. A check list of associated fauna and flora (observed or colleted) , the results of the plankton analysis, granulometry and percentual of chemical elements of the soil (substract) were provided as additional data.